Calcium channels in rat brain synaptosomes: identification and pharmacological characterization. High affinity blockade by organic Ca2+ channel blockers - Turner, TJ (J Neurosci, 1985)
Rat brain synaptosomes are shown to contain functional voltage- sensitive Ca2+ channels that are inhibited by organic Ca2+ channel blockers. Depolarization of synaptosomes with high K+ stimulates uptake of 45Ca2+ which is biphasic in its time course. Replacement of external Na+ with choline eliminates the slower phase of depolarization- stimulated Ca2+ uptake, leaving only a rapid uptake process which terminates within 1 sec. This rapid, tetrodotoxin-insensitive Ca2+ uptake can be inactivated by prior depolarization of the synaptosomes. Depolarization has no effect on the rate of synatptosomal 22Na+ efflux. These results are interpreted as ruling out Na+/Ca2+ exchange as a mediator of the rapid phase of depolarization-stimulated Ca2+ uptake. A portion (30 to 50%) of the rapid phase of depolarization-stimulated Ca2+ uptake is inhibited by nitrendipine, as is depolarization- stimulated [3H]norepinephrine release from synaptosomes. In external Na+, the inhibition constant (Kapp) for nitrendipine inhibition of Ca2+ uptake is 56 nM. The potency of nitrendipine is increased in the absence of external Na+ (Kapp = 1.7 nM), such that inhibition correlates more closely with the equilibrium dissociation constant for [3H] nitrendipine binding to synaptosomes (Kd = 0.35 nM). Other organic channel blockers (nifedipine, verapamil, D600, and dilitiazem) inhibit the rapid Ca2+ uptake. The potencies of all Ca2+ channel blockers tested by us are in reasonable agreement with their potencies, observed in other laboratories, as blockers of Ca2+ channels in smooth and cardiac muscle. These data demonstrate the existence of active voltage- sensitive Ca2+ channels in synaptosomes.(ABSTRACT TRUNCATED AT 250 WORDS)